Project calculation of the steering mechanism hydraulic servo control in motor vehicles - Majkić, Zoran Đukan (Vojnotehnički glasnik / Military Technical Courier, 2013)
Hydraulic servo controls are designed to facilitate rotation in place without providing increased ppower to steering wheels. In the initial design phase, the dimensions required for control systems are usually obtained through the calculation of their load when wheels rotate in place, where the torque is calculated empirically. The starting point in the project calculation is thus to determine the hydraulic power steering torque torsional resistance which is then used to determine the maximum value of force i.e. the torque on the stering wheel. The calculation of the control system servo control consists of determining the basic parameters, the required pump capacity, the main dimensions of the hub and the  pipeline and the conditions for the stability of the system control mechanism. Introduction The aim of the calculation of the steering control system is to determine the basic parameters of its components which ensure the fulfilment of requirements of the control system. Calculations are performed in several stages with a simultaneous  detailed constructive analysis of the control system leading to the best variant. At each stage, design and control calculations of the hydraulic servo of the steering mechanism are performed. The design allows the computation to complete the selection of basic dimensions of the amplifer elements, starting from the approved scheme and the basic building loads of approximate values. Calculations control is carried out to clarify the structural solution and to obtain the output characteristics of the control amplifier which are applied in the  estimation of  potential properties of the structure. Project calculation Baseline data must be sufficiently reliable, ie. must correspond to the construction characteristics of the vehicle design and the control system as well as to service conditions..A proper deterimination of the torque calculation of torsional resistance in wheels is of utmost importance. Moment of resistance to wheel rotation in place The magnitude of the torque required to rotate drive wheels in place, is affected by: 1) load on wheels; 2) coefficient of friction of the tire surface; 3) dimensions and shape of the tire footprint on the surface, as deterimined by the pressure in the tire and its construction; 4) lateral stiffness of the tire; 5) turning radius of drive wheels; 6) angles of inclination of the pin; 7) moment of friction in pins and steering gear mechanism. To achieve the proper torque values of torsional resistance in drive wheels, it is necessary to take into account all these influential factors, as this provides a lower load on the elements in the control system while enabling easier control and reducing the moment of force on the steering wheel. Moment of resistance to rotating drive wheels in place according to Mitin Mitin obtained the coefficient  only for one tire so the use of this formula is practically impossible. Moment of resistance to rotating drive wheels in place according to Taborek Moment of resistance to rotating drive wheels in place according to Lisov This formula takes into account the radius of the tire, but does not take into account the pressure and elastic characteristics of tires. Moment of resistance ito rotating drive wheels in place by Litvinov For the calculation by this formula, it is necessary to know the dependence of the tire footprint surface and the load on it. Moment of resistance to rotating drive wheels in place by Gough Experimental studies have shown that this term is very acceptable. Dimensions of the executive hydraulic cylinder The control amplifier must provide that the wheels rotate in place when the force of the driver on the steering wheel is not above 160 – 200 N in a complete range of the rotation angles from   for the inner wheel to for the outer wheel. Reactive and centering elements of the hydraulic servo control The control system without a hydraulic servo control must have one very important characteristic which is to develop the ability of the driver to feel the road configuration, especially when going around a curve. In order to achieve this, a reactive element is built into the hydraulic servo control, with a task to absorb rapidly drive wheel oscillations during the reverse inclusion of the hydraulic servo control (from the drive wheels to the steering wheel). Determination of the dimensions of reactive elements and the stiffness of centering springs Taking the results of the static analysis into account, the dependence of force and the torsional resistance in drive wheels can be obtained. From this dependence, P can be found  as a function of . Control calculation The control calculation is performed after selecting general elements of the control system and the amplifier.The control  calculation allows the reduction of amplifier dimensions through the transmission gear mechanism, by selecting the   part onto which amplifier force.is applied. Conclusion The calculation of the control system helps in determining the basic parameters of its elements and assemblies, thus providing the control over the vehicle motion. The main input data in calculating hydraulic servo control is the determination of torsional resistance in drive wheels. In order to achieve proper torque values in torsional resistance, it is necessary to take into account  the given influencing factors since this ensures, on the one hand, lower load on the control system elements and, on the other hand, easier control by reducing the force applied to the steering wheel. ECE Regulation № 79 defines the maximum force that can be applied to the steering wheel, so this paremeter of control systems must be taken into account in vehicle design. The piston stroke and the cylinder length are determined for maximum torque angles of drive wheels, followed vy the determination of the cylinder piston diameter. The tendency to reverse the action of the  hydraulic servo control would violate the basic requirement to the control system which is to get drive wheels back into straight line motion under the influence of the stabilizing moment. In order to prevent reverse action, a reactive and centering element is installed into the hydraulic servo control.Prestressing of central springs provides the return of the steering and drive wheels under the influence of the stabilizing moment without involving the hydraulic servo control. Friction force in the control mechanism must be lower than the force of prestressed central springs . The control computation is performed after the determination of all parameters in order to test the operating ability of the hydraulic servo control and to obtain its characteristics. A properly designed hydraulic servo control has to provide that the summary execution of torque hydraulic servo control and the driver exceeds the moment of resistance throughout the range of angles of rotation of wheels.
Keywords: calculation; steering system; steering wheel; Wheels; torque; steering; requirements; projects; Hydraulics